تصميم المحطات الأرضية - علي, صادق حبيب (Latakia University Journal -Engineering Sciences Series, 2019)
يهدف هذا البحث إلى استعراض الطرق المتبعة لحساب وتصميم المحطات الأرضية (الإرسال والاستقبال) والعوامل المؤثرة في تصميم الوصلات الفضائية. من أهم العوامل المؤثرة في الوصلات الفضائية والتي يتناولها البحث هي العوامل التي يمكن التحكم بقيمتها في محطتي الإرسال والاستقبال الأرضيتين. إن التحكم بهذه العوامل يمكننا من تحديد نقطة عمل المستقبل-المرسل أو الترانسبوندر The Transponder في الساتل (القمر الصناعي) بحيث نحصل على أداء أفضل للبث الفضائي والاستفادة القصوى من المجال الترددي الساتلي المستأجر في الساتل. لقد تم في هذا البحث استنتاج معادلات تتعلق فقط بهامش الوصلة النازلة Md وتم حساب جميع محددات الوصلة الفضائية بناء على قيم مختلفة لهذا العامل. كما تمت المقارنة بين وصلات الأنظمة المختلفة التي تستخدم قيما مختلفة لمعدل التصحيح الأمامي للأخطاء Forword Error Correction(FEC) وهي: FEC = 1/2, 2/3, 3/4. لقد تم اقتراح استخدام FEC =7/8 كبديل عن الأنظمة الثلاثة السابقة لما يقدمه هذا النظام من زيادة في كمية المعلومات المرسلة وتحسين نسبة الحامل إلى الضجيج. This research presents the methods used to calculate and to design earth stations (transmit and receive stations) and parameters,which affect the design of satellite links (up and down links). However, the most important parameters,the research deals with,are the parameters that can be controlled by the earth stations.These parameters enable us to define the operation point of the satellite transponder; so that we can get a better performance and maximize exploitation of the rented satellite band. In this research equasions related to margin of down link(only) have been deduced and all the link parameters have been calculated according to different values concerning this parameter. The research also compare between the different link systems, wich use different rates of forword error correction(FEC): FEC=1/2,2/3,3/4). Finally, the research recommends the use of FEC =7/8 instead of the three previous system in order to increase the amount of transmitted information and improve carrier –to-noise ratio C/N.